22 Young Scholar Talk PHD: Investigating Ovine Mastitis: Microbial Sources and Management Methods to Reduce the Prevalence. (22nd October 2022) - Knuth, Ryan; Woodruff, Kelly; Hummel, Gwendolynn; Williams, Jordan; Austin, Kathleen J; Stewart, Whit C; Cunningham-Hollinger, Hannah C; Bisha, Bledar
Abstract: Subclinical mastitis, a common intramammary disease in sheep production, can be costly to producers due to compromised performance and decreased longevity. Our research focused on preventative and therapeutic measures on mammary health where the objectives were to identify (1) the impact of Zn supplementation on the milk microbiome and (2) the impact of management practices at lambing and weaning on prevalence and cure rate of subclinical mastitis, the milk microbiome, and levels of antimicrobial resistance in milk bacteria. In study 1, the milk microbiome was characterized during the first 3 wk of lactation and at weaning in ewes divergent in dietary Zn supplementation (1× = CON or 3× recommendations = ZnTRT). Mammary health was assessed using somatic cell count (SCC) class. Amplicon sequencing revealed the presence of Staphylococcus, Mannheimia, Corynebacterium, and Pseudomonas, all major mastitis pathogens. Effects of breed, dietary Zn concentration, and SCC class on diversity were limited to early lactation, where CON milk had greater composition stability than ZnTRT milk (P = 0.02). In study 2, milk bacteria were characterized by culture; Staphylococcus spp. and Streptococcus spp. were tested for antimicrobial susceptibility. Subclinical mastitis prevalence ranged from 22–66% where coagulase-negative staphylococci (CoNS; 59%), bacilli (35%), Mannheimia haemolytica (10%), S. aureus (8%), streptococci (5%), and Corynebacterium spp. (5%) were common. Milk samples were compared by jug bedding treatment: jugs were cleaned and dried with barn lime before adding fresh straw (CLEAN) or fresh straw was added atop soiled bedding (SOILED). Bedding had no effect on subclinical mastitis (P = 0.57), but CoNS had greater sulfadimethoxine resistance in SOILED isolates (P = 0.03). Additional mastitis control methods at weaning were evaluated: penicillin injection (PENN), restricted feed access (FAST), or their combination (COMBO). Weaning treatment did not affect cure rate from weaning to 3-d post- weaning (P = 0.21). Further characterization of these samples via microbial sequencing are underway with source tracking analyses to investigate an exogenous route via retrograde transfer and environmental bacteria or endogenous route via an entero-mammary pathway. Results support that breed, animal husbandry, and mammary health variably affect the milk microbiome and provide novel insight to the impact of management practices in a milk microbiome longitudinal study.